2022
DOI: 10.1039/d2ra03864a
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the chemistry of β-aminoketones

Abstract: The current study highlighted the significance of β-aminoketones as privileged biologically active molecules, recent synthetic strategies, and synthetic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 170 publications
0
5
0
Order By: Relevance
“…Taking into account the pivotal role of β-aminoketones in organic synthesis, as they are considered one of the most important scaffolds in the preparation of natural products, drugs and bioactive molecules, 18 and once we have set the best reaction conditions that allow the selective conversion of benzonitrile (1a) into β-aminoketone 5a ( Scheme 5 ), we finally decided to focus our attention on the study of the role of the nature of the starting nitriles in this synthetic protocol ( Scheme 6 ). In this case, we found that the electronic properties of the substituents present in the starting aromatic nitriles under study indeed played a pivotal role.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account the pivotal role of β-aminoketones in organic synthesis, as they are considered one of the most important scaffolds in the preparation of natural products, drugs and bioactive molecules, 18 and once we have set the best reaction conditions that allow the selective conversion of benzonitrile (1a) into β-aminoketone 5a ( Scheme 5 ), we finally decided to focus our attention on the study of the role of the nature of the starting nitriles in this synthetic protocol ( Scheme 6 ). In this case, we found that the electronic properties of the substituents present in the starting aromatic nitriles under study indeed played a pivotal role.…”
Section: Resultsmentioning
confidence: 99%
“…54 In the first case, 3-chloro-1-arylpropan-1-ones were transferred into the unsaturated ketones by HCl molecule elimination in the presence of ammonium acetate. The formed intermediate reacted with ammonium acetate through the aza-Michael step to form intermediate A-5 (“β-aminoketone intermediate, 55 C–N bond formation”). The ketosteroid 34 subsequently underwent imino-condensation in the reaction with intermediate A-5 to form intermediate B-5 , which was transformed into the enamine form “ C-5 ” with the aid of acetate anions in the solution.…”
Section: Synthesis Of Pyridines Fused To Steroidal Skeletonmentioning
confidence: 99%
“…This review aims to highlight an example of polycyclic compounds containing the pyrimidine and pyridine cores of distinct biological significance. Through our previous research on the study of the importance of reactive synthons in the preparation of many heterocycles [ 24 , 25 ] and many reviews that discussed the chemistry of related fused pyrimidine [ 26 33 ] and pyridopyrimidine compounds [ 34 36 ], we discuss here the recent advancements on the chemistry of pyridodipyrimidine compounds. The subject of the research is concerned with studying the biological impacts and the distinct preparation approaches for this class of compounds in recent years.…”
Section: Introductionmentioning
confidence: 99%